Creative Activities for Work Teams and Communities of Practice. A guid e for designing participatory, productive, and engaging sessions - AKF (2023)
This free guide aims to build the skills and confidence of people desi gning and facilitating participatory, productive, and engaging worksho p sessions for work teams and communities of practice by providing the m with a series of creative activities that can be run in-person or vi rtually. By the time they have gone through this guide, session leads will be able to: Describe ways in which creative activities can be of value to teams and communities of practice, Design both in-person and virtual workshop sessions that incorporate creative activities, Facili tate participatory, productive and engaging workshop sessions that inc orporate one or several creative activities, and Lead an effective deb rief following a creative activity. This toolkit was developed by the Aga Khan Foundation.